A Compact 0.73~3.1 GHz CMOS VCO Based on Active-Inductor and Active-Resistor Topology - Pakasiri, Chatrpol; Hsu, Ke Chung; Wang, Sen (My University, 2024)
In this paper, a wideband VCO that covers popular Long-Term Evolution (LTE) 0.7 GHz and LTE 2.6 GHz frequencies is designed and developed in a standard 0.18 μm CMOS process. The VCO utilizes active inductors to achieve coarse-tuning of the inductance and a compact chip area. Moreover, an active feedback resistor is introduced into the active inductor for fine-tuning of the inductance. The feedback resistor also affects the equivalent resistance of the active inductor; therefore, wide inductance tuning and low power consumption can be obtained by optimizing the resistor. The core area of the fabricated CMOS chip is merely 0.046 mm2, excluding all testing pads. With a 6.7~10.1 mW DC consumption, the measured oscillation frequencies range from 0.73 GHz to 3.1 GHz, which demonstrates a 123.8% tuning range. At the frequencies of interest, the measured phase noises are from −80.7 to −84.5 dBc/Hz at a 1 MHz offset frequency.
Keywords: active inductor; active resistor; CMOS; voltage-controlled oscillator (VCO); wide-tuning range